Influence of irradiation on collagen content during wound healing in diabetic rats (Pesquisa Odontológica Brasileira, 2002)
The aim of the present experimental research was to investigate the effects of electron irradiation on the collagen content and on the organization of the granulation tissue of skin, in diabetic rats. In this study, 48 Wistar rats were assigned to 4 groups: control, irradiated, diabetic and irradiated diabetic. First, diabetes mellitus was induced in the last two groups, by means of a single intravenous injection of streptozotocin. Fifteen days later, all animals underwent a surgery in order to create an excisional wound on their anterior dorsal skin. On the third post-operative day, only an approximately 1-cm-wide area around the wounds was exposed to 1 Gy of 6 MeV electron beam radiation, which was delivered in a single dose. Wound healing was examined by means of polarized light microscopy at 4-, 7-, 13- and 21-day time intervals after wounding. Based upon an essentially qualitative evaluation, it was possible to conclude that local electron irradiation and diabetes' associated dysfunctions caused a decrease in the collagen content of newly-formed tissue, which was more pronounced in irradiated diabetic animals. The macromolecular organization of granulation tissue was delayed in irradiated, diabetic and irradiated diabetic animals, in relation to what was observed in control animals.